2000
DOI: 10.1128/jvi.74.8.3918-3923.2000
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Incorporation of HLA Class II onto Human Immunodeficiency Virus Type 1 Requires Envelope Glycoprotein Packaging

Abstract: HLA class II DR is one of the most abundant cell surface proteins incorporated onto human immunodeficiency virus type 1 (HIV-1) during budding. The mechanism for HLA class II protein incorporation is not known and may involve a viral protein. To determine whether Env affects HLA class II protein incorporation, HIV-1 virions, either with or without Env on their surface, were produced from HLA class II-expressing cells and analyzed by whole-virus immunoprecipitation with antisera against HLA class II proteins. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
1
19
1
Order By: Relevance
“…There may be structural constraints imposed by the virion-encoded proteins leading to selectivity of host cell molecule incorporation. For example, incorporation of MHC class II may require association with gp41 and the incorporation of MHC class I is haplotype dependent (Poon et al, 2000). This may, at least in part, explain the species specificity reported in the present study.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…There may be structural constraints imposed by the virion-encoded proteins leading to selectivity of host cell molecule incorporation. For example, incorporation of MHC class II may require association with gp41 and the incorporation of MHC class I is haplotype dependent (Poon et al, 2000). This may, at least in part, explain the species specificity reported in the present study.…”
supporting
confidence: 62%
“…MHC molecules are present in virions at levels exceeding gp120/ gp41 (Henderson et al, 1987;Arthur et al, 1992) and are incorporated non-randomly (Hoxie et al, 1987;Poon et al, 2000;Nguyen & Hildreth, 2000). Furthermore, it has been shown that incorporation of HLA-DR by clinical isolates of HIV-1 expanded in primary human cells depends on the producing cell and the donor source (Cantin et al, 2001).…”
mentioning
confidence: 99%
“…It is well documented that high levels of MHC class I and MHC class II are incorporated into HIV-1 virions grown in vitro (5,14,66,74) or isolated from patient plasma (42) and that the incorporation of envelope glycoproteins and MHC molecules into virions is linked (62). The hypothesis that HIV is capable of evading the immune response by incorporating MHC molecules into its envelope is not unprecedented.…”
Section: Discussionmentioning
confidence: 99%
“…But like many processes in biology, the incorporation of cellular proteins into the external lipid bilayer of a lentivirus likely occurs through several different mechanisms, as it seems to be cell type and virus strain dependent, at least under in vitro conditions (23,24,67,82). One study reported a direct interaction between virion-incorporated HLA-DR and a 43-amino-acid domain located in the cytoplasmic tail of HIV-1 transmembrane envelope glycoprotein gp41 (84). In contrast, incorporation of ICAM-1 was found to be independent of HIV-1 envelope glycoproteins (7).…”
Section: Host Cell Proteins Located On Virusesmentioning
confidence: 99%